Effect of Incorporation of Aluminium Waste in Concrete Matrix Using Different Mix Ratio and Water Cement Ratio - MBADIKE, ELIVS M. (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
The research investigated the effect of incorporation of aluminum waste in concrete matrix using different mix ratio and water cement ratio. Aluminum waste which was obtained from Aluminum Extrusion Industry (ALEX) Inyishi in Ikeduru Local Government Area of Imo State, Nigeria was investigated. Concrete Cubes with different ingredient components, mix ratio and water cement ratio were used to cast cube samples. The cubes have a dimension of 150mm x 150mm x 150mm. The cube samples were tested for 7, 14 and 28days strength. The total of 216 concrete cubes were cast. The result showed that the addition of 5% Aluminum waste to a standard 1:2:4:0.55 mix caused the compression strength of the concrete to rise from 26.07N/mm2 to 28.47N/mm2 .This result represents an increase of 9.21% in compressive strength. The initial and final setting time of the Ordinary Portland Cement (OPC) used is 53mins and 587mins respectively. The slump test of aluminum waste concrete at different water cement ratio using 1:2:4 mix ranges from 4-20mm while that of 1:3:6 mix ranges from 7-14mm.